The Effect of Hyaluronidase as an Adjuvant to Local Anaesthetics in Peripheral Nerve Stimulator-guided Supraclavicular Brachial Plexus Block: A Randomised Controlled Study - Tejash H Sharma; Jainy Shah; Amit Chauhan; Dushyant Chavda; Sara Mary Thomas (Journal of Clinical and Diagnostic Research, 2024)
Introduction: For upper limb procedures using the supraclavicular approach to brachial plexus block, various adjuncts to Local Anaesthetics (LA) have been employed to improve the quality and duration of anaesthesia and postoperative analgesia without leading to any adverse sideeffects or prolonging the period of motor block. Hyaluronidase is an enzyme used with other drugs to accelerate their dispersion and distribution. It catalyses the hydrolysis of a component of the extracellular matrix, hyaluronan, thereby lowering its viscosity and improving tissue permeability. Aim: To evaluate the sensory and motor blockade resulting from the addition of hyaluronidase as an adjuvant to LA in Peripheral Nerve Stimulator (PNS)-guided Supraclavicular Brachial Plexus Block (SBPB). Materials and Methods: This prospective, comparative, double-blinded, randomised controlled study was conducted in a Department of Anaesthesiology S.B.K Shah Medical Institute and Research Centre, Vadodara, Gujarat, India at a tertiary care hospital on 72 patients undergoing elective upper limb surgeries under PNS-guided SBPB over 18 months from November 2022 to August 2024. Group B (n=36) received inj. bupivacaine (0.5%) 13 mL, inj. lignocaine with adrenaline (2%) (1:200,000) 13 mL, and inj. normal saline (0.9%) 4 mL, for a total of 30 mL, and Group H (n=36) received inj. bupivacaine (0.5%) 10 mL, inj. lignocaine with adrenaline (2%) (1:200,000) 10 mL, inj. hyaluronidase (900 IU) 6 mL, and inj. normal saline (0.9%) 4 mL, for a total of 30 mL. Sensory and motor blockade and rescue analgesia were recorded at 0, 1, 3, 5, 7, and 10 hours. Categorical variables were analysed using the Chi-square test. To analyse continuous variables, the student’s t-test was used. The p-value of less than 0.05 was deemed statistically significant. Results: The onset time of sensory and motor block was earlier with Group H (2.36±0.25 minutes and 4.2±0.29 minutes) than with Group B (4.54±0.25 minutes and 6.51±0.29 minutes), respectively (p<0.05). The sensory and motor block lasted longer in Group B (278.8±7 minutes and 266.8±6.78 minutes) than in Group H (263.2±7 minutes and 246.3±6.78 minutes) respectively, p<0.05. The duration of analgesia was longer with Group B (240.8±7.84 minutes) compared to Group H (220±7.84 minutes) p<0.05. No major adverse effects were observed. Conclusion: Addition of hyaluronidase to a lower volume of LA results in rapid onset of the block with minimal side-effects.